Towards Realistic and Flexible Advance Care Planning - O'NEILL, DESMOND (My University, 2013)
The suffering of the many Irish people who bought houses at the height of the economic boom with variable mortgages is a topical and telling demonstration of the difficulties of planning for the future. What seemed like a good idea in 2006 has become a millstone around many necks, putting huge strains on marriages and family life, and is deservedly a topic of national debate. Signing into a binding written commitment for their financial future has been a bitter experience for this large group of people: how much more painful might it be if they had signed into unhappy binding agreements about their future healthcare? The illusion that the future healthcare can be tightly defined is typified by the case for advance directives, an idea for which enthusiasm has unhappily out-stripped an increasingly critical biomedical literature1. This ranges from their description by the majority of ICU staff in one US study as ‘useless’ to clear problems which arise when advance directives are patently in conflict with the patient’s best interests
PUBLISHED
Keywords: Care planning; Ageing; Neuroscience; Arts and Humanities and Healthcare; Biomedical Ethics; Medical Humanities